Public Understanding of the Implementation of Islamic Law in the Context of Modern Life in Indonesia - Komaruddin, Koko; Sarib, Suprijati; Mokodenseho, Sabil; Mokodompit, Nurcahyani; Manangin, Tindra (Eastasouth Institute, 2024)
This qualitative research explores people's understanding of the application of Islamic law in the context of modern life in Indonesia. As the country with the largest Muslim majority population in the world, Indonesia is a unique case study to see the intersection between Islamic law and the dynamics of contemporary society. Through in-depth interviews and thematic analysis, this study explores the diverse perspectives, beliefs and experiences of Indonesian individuals regarding Sharia principles and their relevance in today's society. The findings highlight the complexities of reconciling religious norms, cultural traditions, and modern realities in Indonesian society, and provide insights for policymakers, scholars, and civil society actors seeking to promote social cohesion, religious tolerance, and legal reform.